(untitled) (Journal of Hama University, 2024)
This study aims to identify the relationship between psychological immunity and decision-making and to identify the differences between second and final year students in the Psychological Counseling Department at the Faculty of Education - Damascus University in psychological immunity and decision-making according to the gender variable (male and female), and the school year variable (second and final year). The sample of the study consisted of (322) male and female students from the second and final year students in the Department of Psychological Counseling at the College of Education - Damascus University, divided into (216) second years and (106) last years, who were chosen in a stratified random manner from the College of Education at Damascus University. The psychological immunity scale prepared by Connor-Davidson was applied to them, and the decision-making scale prepared by Youssef Abdoun. The results of the study indicated: - The presence of psychological immunity and decision-making among the study sample individuals to a moderate degree. - There is a statistically significant positive correlation between psychological immunity and decision-making among the study sample, and the correlation value was (0.74). - There are no statistically significant differences between males and females in psychological immunity. - There are statistically significant differences between males and females in decision-making in favor of male students. - There are statistically significant differences between the second and final year students in psychological immunity in favor of the last year. - There are statistically significant differences between second and last year students in decision-making in favor of the last year.